CCN2 (Cellular Communication Network Factor 2) Deletion Alters Vascular Integrity and Function Predisposing to Aneurysm Formation. Issue 3 (30th December 2021) - Rodrigues-Díez, Raúl R.; Tejera-Muñoz, Antonio; Esteban, Vanesa; Steffensen, Lasse B.; Rodrigues-Díez, Raquel; Orejudo, Macarena; Rayego-Mateos, Sandra; Falke, Lucas L.; Cannata-Ortiz, Pablo; Ortiz, Alberto; Egido, Jesus; Mallat, Ziad; et al.
Abstract : Supplemental Digital Content is available in the text. Abstract : Background: CCN2 (cellular communication network factor 2) is a matricellular protein involved in cell communication and microenvironmental signaling responses. CCN2 is known to be overexpressed in several cardiovascular diseases, but its role is not completely understood. Methods: Here, CCN2 involvement in aortic wall homeostasis and response to vascular injury was investigated in inducible Ccn2 -deficient mice, with induction of vascular damage by infusion of Ang II (angiotensin II; 15 days), which is known to upregulate CCN2 expression in the aorta. Results: Ang II infusion in CCN2-silenced mice lead to 60% mortality within 10 days due to rapid development and rupture of aortic aneurysms, as evidenced by magnetic resonance imaging, echography, and histological examination. Ccn2 deletion decreased systolic blood pressure and caused aortic structural and functional changes, including elastin layer disruption, smooth muscle cell alterations, augmented distensibility, and increased metalloproteinase activity, which were aggravated by Ang II administration. Gene ontology analysis of RNA sequencing data identified aldosterone biosynthesis as one of the most enriched terms in CCN2-deficient aortas. Consistently, treatment with the mineralocorticoid receptor antagonist spironolactone before and during Ang II infusion reduced aneurysm formation and mortality, underscoring the importance of the aldosterone pathway in Ang II–induced aorta pathology. Conclusions: CCN2 is critically involved in the functional and structural homeostasis of the aorta and in maintenance of its integrity under Ang II–induced stress, at least, in part, by disruption of the aldosterone pathway. Thus, this study opens new avenues to future studies in disorders associated to vascular pathologies.